EFEKTIVITAS PEMBELAJARAN PAI DENGAN MODEL SNOWBALL THROWING - Siti Nurhanah; Taukhid Mubarok (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The writing of this article is motivated by the behavior and interest of students during learning which is still low and tends to be reluctant to pay attention to the material given by the teacher. Therefore, the researcher raised the title of the snowball trowing method. The snowball trowing method is a snowball throwing method. The purpose of this observation is to understand and describe the effectiveness of the snowball throwing method in PAI lessons in grade VI SDN Kluwut 02. The method carried out in this observation is qualitative with a descriptive approach. The target of this field observation activity is Class VI students of SDN Kluwut 02 with a form of descriptive qualitative research, where research decisions are displayed in a descriptive narrative format. This observation community is all grade VI students of SDN Kluwut 02. The method of data collection is carried out using studies, interviews, and documentation. The combined data is raised. The results of this observation state that learning by applying the snowball trowing method can foster the behavior and learning desire of elementary school students. The use of the snowball trowing method makes learning more interesting and feels different before and after using the media. The atmosphere of the learning process makes it more comfortable and makes students more involved during the lesson. Thus learning activities are carried out in a quality manner and learning effectiveness is intertwined and achieved.